Pengabdian Kebidanan Komunitas pada Ny. “H” dengan Bendungan ASI di Lombok Tengah - Destri Sri Ramdani; Gladeva Yugi Antari; Baiq Sri Sulantri (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
Breast milk engorgement is a common problem experienced by postpartum mothers, particularly during the early puerperium period, and may lead to complications such as mastitis, decreased milk production, and ineffective breastfeeding if not properly managed. This community service activity aimed to improve maternal knowledge and skills in managing breast milk engorgement through comprehensive midwifery care. The activity was conducted using the Varney midwifery management approach, including assessment, diagnosis, planning, implementation, and evaluation. The subject of the activity was a postpartum mother on day three with breast engorgement. Interventions included health education about breast engorgement, demonstration of correct breastfeeding techniques, breast care education, warm compresses before breastfeeding, cold compresses after breastfeeding, breast massage, and encouraging frequent breastfeeding every two hours. Monitoring was conducted for two days to evaluate maternal condition and breastfeeding effectiveness. The results showed measurable improvements, including reduced breast pain, decreased breast tension, smoother milk flow, and increased breastfeeding frequency from 3–4 times per day to 8–10 times per day. Additionally, the mother was able to demonstrate correct breastfeeding techniques independently, and no complications such as mastitis were observed. These findings indicate that individualized education combined with practical demonstrations effectively improves maternal skills and resolves breast engorgement. The implementation of comprehensive midwifery care using the Varney management approach proved effective in preventing complications and improving breastfeeding outcomes in postpartum mothers.